Transition from Pervasive Developmental Disorders to Autism Spectrum Disorder: Proposed Changes for the Upcoming DSM-5 - Banu Tortamis Ozkaya (Psikiyatride Güncel Yaklaşımlar, 2013)
American Psychiatry Assosiation has scheduled to release The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) in May 2013. According to the main changes being proposed about autism, there will be one unified Autism Spectrum Disorder diagnosis in the DSM-5 classification. This unified diagnosis will eliminate the distinct diagnostic categories under Pervasive Developmental Disorders in the DSM-IV-TR, namely autistic disorder, asperger syndrome, pervasive developmental disorder-not otherwise specified, and childhood disintegrative disorder. Rett syndrome will be excluded from autism spectrum disorder due to its genetic basis. In addition, severity of symptoms will be measured among individuals with autism spectrum disorder based on the support level required due to the impairment in their lives. The basic rationale behind this revision is that it is better to conceptualize autism as a spectrum including various individuals whose symptoms in different developmental areas range from mild to severe. It is aimed to increase the specificity of autism diagnosis by using one single diagnostic category with its specified severity rather than differentiating several subtypes. The major concern raised over the DSM-5 proposal has been the possibility that some of the individuals who were diagnosed with pervasive developmental disorder according to the DSM-IV-TR might not get a diagnosis in this new system. After the DSM-5 is released, clinical, legal, and educational rearrengements regarding the use of new autism spectrum disorder diagnostic criteria are expected to accelerate worldwide and in Turkey. This paper aims to review briefly the upcoming autism spectrum disorder diagnosis planned to appear in the DSM-5, the rationale of the proposed revision, main critics to the DSM-5 draft that has been publicized, and some of the regulations expected to occur in practice after the changes.